Academic Adjustment of Freshmen in Cambodian Higher Education Institutions: A Systematic Literature Review - Lan, Bunrosy; Sam, Rany; Keo, Vireak; Roeut, Wen (Journal of General Education and Humanities, 2024)
First-year students face experiences in the primary adjustment stages with their transition to pre-university enrollment, and the experiences are typically highlighted as challenges that will be concentrated significantly in this systematic literature review. This systematic literature review critically synthesizes 20 published articles from 2014 to 2023 on the academic adjustment of first-year students in Cambodian higher education institutions. The qualitative study methods and exploratory design are used, and researchers compiled and evaluated relevant literature focusing on challenges faced by first-year students, factors influencing adjustment, strategies for academic adjustment, and outcomes of adjustment interventions. Data were gathered from reliable databases, and articles meeting predefined criteria were subjected to thematic analysis using Clark and Braunne's Thematic Analysis model. Findings highlight first-year students' challenges, such as academic performance, social identity issues, financial constraints, and language barriers. Factors influencing adjustment include social, personal-emotional, and institutional aspects, underlining the significance of social support and coping strategies. Strategies for academic adjustment focus on effective time management, utilizing support services, and maintaining a healthy work-life balance. Intervention outcomes aim to enhance first-year students' retention rates, mental health, and academic success. Qualitative research emerged as the predominant approach, enabling researchers to understand nuanced experiences and perspectives.